Nexus Between Artificial Intelligence, Consumer Behavior, Consumer Experience, and Purchase Intention: A Case from Shenzhen, China - Yuchen, Song; Ying, Wang (El profesional de la informacion, 2024)
This research aimed to investigate the influence of consumer behaviour (COB), artificial intelligence technology, and satisfying consumer experience on purchase intention (PIN). The study investigates the direct and moderating effect of hedonic motivation on the relationship between consumer behavior, artificial intelligence, satisfying consumer experience, and purchase intention for the respondents, residents in Shenzhen, China. A survey questionnaire based on past studies was finalized with a slight modification to cover the study context and key variables. Demographic factors included gender, education, and age distribution of the sample of 437 residents with experience of artificial intelligence technology, related products, and their subsequent purchase intention. The analysis showed model's substantial explanatory power with the help of R-square value of 0.842. The outer model assessment by using the Smart PLS confirmed that variables captured enough variance (average variance extracted), internal consistency reliability, and discriminant validity. The inner model assessment confirmed that artificial intelligence, consumer behaviour, and hedonic motivation directly influenced purchase intention. The interactive effect of hedonic motivation confirmed a significant presence in the relationship between artificial intelligence and purchase intention and between COB and PIN. The suggestions and limitations are well captured by the end of this research.